2012
DOI: 10.1016/j.neurenf.2012.04.487
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity of adolescents with high functioning autism in response to emotional words and facial emoticons

Abstract: Studies of social dysfunction in patients with autism spectrum disorder (ASD) have generally focused on the perception of emotional words and facial affect. Brain imaging studies have suggested that the fusiform gyrus is associated with both the comprehension of language and face recognition. We hypothesized that patients with ASD would have decreased ability to recognize affect via emotional words and facial emoticons, relative to healthy comparison subjects. In addition, we expected that this decreased abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…19 The thalamus, which plays a central role in cognitive, sensory, and emotional information processing, is involved in several diseases, such as depressive disorder. 20 Brain imaging studies have shown that the fusiform gyrus is involved in language comprehension and facial recognition, 21 and the left lingual gyrus is associated with the relevant visual imagery, 22 while the right lingual gyrus is related to predictive inference generation. 23 Papez circuit is a neural loop including the hippocampus, mammillary bodies, anterior thalamic nuclei, and posterior cingulate region, which is critical for the consolidation of declarative memory.…”
Section: Discussionmentioning
confidence: 99%
“…19 The thalamus, which plays a central role in cognitive, sensory, and emotional information processing, is involved in several diseases, such as depressive disorder. 20 Brain imaging studies have shown that the fusiform gyrus is involved in language comprehension and facial recognition, 21 and the left lingual gyrus is associated with the relevant visual imagery, 22 while the right lingual gyrus is related to predictive inference generation. 23 Papez circuit is a neural loop including the hippocampus, mammillary bodies, anterior thalamic nuclei, and posterior cingulate region, which is critical for the consolidation of declarative memory.…”
Section: Discussionmentioning
confidence: 99%